Legal Protection of Trade Secrets, Industrial Design And Integrated Circuit Layout Design In Indonesia - Ali, Bujang; Jaya, Dipo Setia Hady Akbar; BA, RS Mohammad Al Amin; Fahlevi, Muhammad Reza; Acong, Acong (Bacarita Law Journal, 2024)
The government of Indonesia is compelled to bring national rules for the protection of intellectual property rights into line with international norms as a result of the ratification of TRIPs. This study employs a qualitative descriptive research strategy rooted on normative legal theory. In order to assess how well national laws have met the international requirements set forth by TRIPs, data was gathered via literature reviews of primary, secondary, and tertiary legal sources. This study's overarching goal is to determine how well Indonesia's various laws pertaining to IPR—such as those pertaining to trade secrets, industrial design, and integrated circuit layout design—are in sync with the provisions of the TRIPS Agreement. The findings demonstrate that these three statutes have significantly incorporated the fundamental elements governed by TRIPs. Trade secret and integrated circuit layout design protection periods, for instance, have been tweaked to meet the bare minimum requirements imposed by TRIPs. Furthermore, national legislation have also strictly governed the exclusive rights that intellectual property holders have, such as the ability to sue for damages in a civil court and get compensation, and the criminal penalties that those who violate these rights face. Nevertheless, there were obstacles to proper legal enforcement and execution in the field, particularly with regard to the level of legal knowledge among corporate players and the general public, as this study also revealed. As a result, this study significantly advances the cause of bringing Indonesian intellectual property legislation up to par with global norms. To maximize the advantages for innovation and economic development that current legislation may provide, Indonesia has to adopt strategic initiatives including bolstering law enforcement and raising public understanding about the significance of preserving intellectual property rights.